Measurement of Radon Exhalation Rate in some consuming Foodstuff in some Local Markets - Jameel, Athraa Naji (Iraqi Journal of Science, 2025)
This research aimed to evaluate the radon concentration for 11 different samples of consuming foodstuff collected from the markets. Alpha- CR-39 track detectors were used to analyze the radium concentration and radon exhalation rate. Al-Sayed coffee powder had the highest radon concentration of 99.7 Bq/m3 , while Al-Warda sugar had the lowest concentration of 56.5 Bq/m3 . The surface exhalation rate for the powdered milk samples varied from 2.3Bq/ m2 .h in Al-Marai sample to 3.5 Bq/m2.h in sample Anchor. While the coffee powder samples ranged from 2.4 Bq/ m2 .h in sample Al-Rifai to 3.7 Bq/m2 .h in sample Al-Sayed. The sugar samples varied from 2.11 Bq/ m2 .h in sample Al-Warda to 2.3 Bq/m2 .h in sample Al-Usra. The lifetime cancer risk was found to be within the range of 28-44.8 people per million with a mean value of 36.5±0.5 for powdered milk, and within the range of 29.5-45.1 people per million with a mean value of 38±0.5 for coffee powder and the range of 25.5-28 people per million with a mean value of 26±0.07 for sugar sample. The samples measured are mainly used by consumers and do not contain harmful radioactivity.